IMMU-10. NIVOLUMAB IN THE TREATMENT OF RECURRENT OR REFRACTORY PEDIATRIC BRAIN TUMORS: A SINGLE INSTITUTIONAL EXPERIENCE. Issue 2 (22nd June 2018) - Gorsi, Hamza; Malicki, Denise; Khanna, Paritosh; Elster, Jennifer; Barsan, Valentin; Tumblin, Mark; Yeh-Nayre, Lanipua; Milburn, Mehrzad; Crawford, John
Abstract: Tumor cells evade immune-mediated destruction through activation of checkpoints. Successful use of the immune checkpoint inhibitors in certain cancer types has generated interest in using this approach in pediatric brain tumors. Ten consecutive children (6 boys, 4 girls, mean age 11 years, range 2-17 years) with pediatric recurrent or refractory pediatric brain tumors (4 high grade glioma, 2 pineoblastoma, 1 disseminated low grade glioma, 1 medulloblastoma, 1 ependymoma, 1 primitive neuro-ectodermal tumor) were treated at Rady Children's Hospital San Diego from 2015-2017 with the immune checkpoint inhibitor nivolumab (3 mg/kg every 2 weeks). Eight had received prior chemotherapy and 9 received prior radiation therapy. Seven had radiographic progression of disease (total 36 doses, mean 3.6 doses) with mean time to progression of 5.4 weeks (range 1.6-13.7 weeks). One patient voluntarily discontinued treatment after stable disease at 24 weeks and 2 patients showed either transient stability or partial response of brain disease but worsening of metastatic disease. There were no dose limiting side effect observed, however there was a 10 % incidence of elevated ALT, hyperglycemia, pancreatitis and hypo-albuminemia. Although the tumor mutation burden (TMB) was low (mean 2, range 0-6.3), there was a trend between TMB and time to progression. PDL-1 immuno-histochemical analysis and next generation sequencing data on each tumor will be presented. Our findings suggest nivolumab is well tolerated in pediatric patients with recurrent brain tumors. Future randomized controlled studies stratifying for TMB may be necessary to demonstrate the efficacy of PD-L1 inhibitors in recurrent pediatric brain tumors.